APLIKASI MURABAHAH PADA LEMBAGA KEUANGAN SYARIAH - Erna Damayanti (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2018)
Abstact The implementation of murabahah concept in syariah bank, if connected to clerical view, experienced some modification. Murabahah practiced in LKS is known as murabahah li al-'mir bi al-syirâ ', a sale and purchase transaction in which a customer comes to the bank to buy a commodity with certain criteria, and he promises to buy the commodity/goods in a murabahah contract, i.e. in accordance with the cost of goods purchased plus the level of profit agreed by both parties. The customer will pay it through periodical installment in accordance with his financial capabilities. The application of murabahah in the practice of Sharia Financial Institutions (LKS) is the transfer of direct ownership from suppliers to customers, whereas direct bank payments are made to the first seller/supplier. The customer as the last buyer receives the goods after having entered into a murabaha agreement with the bank and the LKS conducts murabaha with the customer, and at the same time represents the wakalah contract to the customer to buy the goods themselves. Keywords: Application, Murabahah, LKS (Sharia Financial Institution).